From Getting Out to Vote: Digital Political Narratives and their Effect on Young People's Electoral Decision-making - Rodriguez-Saavedra, Miluska Odely; Donayre Prado, Erick Alexander; Donayre Sarolli, Adolfo Erick (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This research analyzes the symbolic and emotional effects of digital political narratives on youth electoral decision-making within the political-communicative ecosystem of platforms such as TikTok, Instagram, and Facebook. Using a qualitative approach with a digital hermeneutic-ethnographic design, it investigates the ways in which young people interpret viral electoral discourse and construct political meaning. The findings reveal a critical appropriation of emotional and parodic content, where voting is configured more as an act of identity than deliberation. The study shows that, although the candidates managed to capture attention, their messages did not generate sustained credibility; authentic, coherent, and emotionally genuine narratives are required.